C6 Not all IRIS's are equal: a case of sudden death. (23rd May 2012) - Wainwright, E; Chen, F; Tang, A
Abstract : Background: Myocarditis is a well-recognised complication of HIV infection but is seldom observed in clinical practice in the UK. Additionally, myocarditis has been associated with sudden unexplained death in the general population. The mode of death in these cases is likely to involve arrhythmias. We present a very rare case of sudden cardiac death related to HIV-associated myocarditis. Case report: A 47-year-old man was diagnosed with HIV in 2002. He was lost from follow-up between 2006 and 2009, when he re-presented with a CD4 of 10. He commenced HAART in November 2009 and had a good response (CD4 70; viral load <50). In March 2010 he collapsed whilst playing football and a clinical diagnosis of cardiac arrest was made; resuscitation was unsuccessful. Retrospective history from a relative indicated no prodromal illness. A coroner's post-mortem examination indicated cardiac pathology as the most likely cause of death; this was supported by abnormal macroscopic appearance of the cardiac muscle. Histological examination of the myocardium showed focal fibrosis and lymphocytic infiltration. The finding of lymphocytic myocarditis in a previously asymptomatic and well person following 4 months of HAART strongly implicates immune reconstitution inflammatory syndrome (IRIS) myocarditis as the cause of the patient's death. Conclusions: The wide spectrum of IRIS is increasingly familiar to HIV physicians but this case illustrates the need to be aware of potentially fatal forms of IRIS with increased risk in the severely immunosuppressed. Some of these forms unfortunately have no easily discernible manifestations.